2016
DOI: 10.1128/mbio.01072-16
|View full text |Cite
|
Sign up to set email alerts
|

Disease Severity and Immune Activity Relate to Distinct Interkingdom Gut Microbiome States in Ethnically Distinct Ulcerative Colitis Patients

Abstract: Significant gut microbiota heterogeneity exists among ulcerative colitis (UC) patients, though the clinical implications of this variance are unknown. We hypothesized that ethnically distinct UC patients exhibit discrete gut microbiotas with unique metabolic programming that differentially influence immune activity and clinical status. Using parallel 16S rRNA and internal transcribed spacer 2 sequencing of fecal samples (UC, 30; healthy, 13), we corroborated previous observations of UC-associated bacterial div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 46 publications
4
78
0
Order By: Relevance
“…We were able to recapitulate major findings from all studies. For example, we identified disease-specific alterations in multiple studies in Akkermansia 39,31 24,40,39,33,20 and Streptococcus 34 (Fig. 2).…”
Section: Autoimmunity-associated Changes In Microbial Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to recapitulate major findings from all studies. For example, we identified disease-specific alterations in multiple studies in Akkermansia 39,31 24,40,39,33,20 and Streptococcus 34 (Fig. 2).…”
Section: Autoimmunity-associated Changes In Microbial Compositionmentioning
confidence: 99%
“…Following quality control (QC) and filtering, 20 16S rRNA studies remained for downstream analysis (Fig. 1) 19,20,[22][23][24][26][27][28]30,31,[33][34][35][36][37][38][39][40]46,47 . Notably, 8 out of the 20 studies used investigated the role of the human gut microbiome in IBD, due in part to its relatively high prevalence in 1.3% of US adults 48 .…”
Section: Autoimmunity-associated Changes In Microbial Compositionmentioning
confidence: 99%
“…The majority of these studies revealed a decrease in overall bacterial diversity in NAFLD, similar to that reported in obesity. (80) However, as for other chronic diseases, (81)(82)(83) human microbiome studies in NAFLD have not identified a unique microbial signature. The most consistent finding among studies is that higher disease severity, and in particular advanced fibrosis, is associated with enrichment of members of the Bacteroides and Escherichia genera.…”
Section: The Gut Microbiome In Nafldmentioning
confidence: 99%
“…UC is rarely observed in smokers, as nicotine/nicotinic receptor agonists suppress colitis [4]; however, the mechanism by which cigarette smoke/nicotine suppresses the development of UC is unclear. UC is primarily a Th2-mediated IBD associated with eosinophilic infiltration and overproduction of Th2 chemokines/cytokines including eotaxin (CCL11), IL-5, and IL-13 [5][6][7]. In animal models, activation of pulmonary nicotinic acetylcholine receptors (nAChRs) moderates eosinophilic infiltration through suppression of Th2 responses [8].…”
Section: Introductionmentioning
confidence: 99%
“…MUC2, the predominant mucin in the gut, plays a critical role in gut homeostasis, and MUC2deficient mice develop colitis spontaneously [13]; however, unlike MUC5AC in bronchial epithelial cells [14], IL-13 does not always stimulate MUC2 [15]. UC also affects gut microbiota and the integrity of the epithelial barrier in the colon [2,5,6]; thus normal fecal microbial transplantation is a promising treatment for UC [16,17]. As DSS has been found to induce UC-like conditions in a mouse model [18,19], in this study we examined whether PB attenuated DSSinduced colon pathology in C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 99%